The Targums in the light of traditions of the Second Temple period - Legrand, Thierry.; Joosten, Jan. (Supplements to the Journal for the Study of Judaism, 2014)
Although the Jewish Targums were written down only from the second century CE onward, and need to be studied against their Late Antique background, the issue of their connection to earlier sources and traditions is an important one. Do the existing Targums link up with an oral translation of Scripture and, if so, how far does it go back? Do the Targums transmit traditional exegetical material in a distinct form? What is the relation between the Targums and \'parabiblical\' literature of the Second Temple period (including the New Testament)? In the present volume, these and other questions are studied and debated by an international group of scholars including some of the best specialists of Targumic literature in all its diversity, as well as specialists of various Second Temple writings.